Formation model for future physical education teachers’ professional activity of individual style under teaching internship course (Professional Pedagogics, 2018)
This article deals with the content of the model of formation of the individual style of professional activity of future physical training teachers in the process of teaching practice. The pedagogical conditions that directly influence the effectiveness of this process are determined and substantiated. The designed model is specified by the components of the methodology and target, organization and content and diagnostic blocks, which reflect the purpose of the educational process, defined by taking into account civilization needs and social order. The block of methodology and target contains the basic idea, which subordinates all the constituent elements of the model and determines the ability to observe the overall progress and adjust it in advance. It defines the strategy for the model implementation and includes the purpose, methodological principles and universal approaches to the style formation. The block of organization and content reveals the component composition of the individual style of professional activity; a complex of the conditions, forms, methods and means of work that ensure the effectiveness of the model implementation. A set of external and internal causes, driving forces and phenomena, some features of the process of establishment an individual style of the future teacher are described in this block.
Keywords: model; teacher of physical training; teaching practice; individual style of professional activity